The impact of tourism firm's philanthropy decision on its business objective. Issue 5 (August 2018) - Wang, Keling; Lin, Chien-Pang; Chen, Ming-Hsiang; Gillard, Evelina
This study explains the impact of tourism firm's corporate philanthropy (CP) decision on its business objective in a competition environment from a strategic management perspective. Key results are summarized as follows. First, tourism firms can use CP as an effective strategy to compete for higher sales revenue and achieve their organizational objective of higher profit if CP generates market competitiveness. Second, if only one of the two competing tourism firms gives to charity and CP generates market competitiveness, the tourism firm's giving will deteriorate its competitor's performance. Third, if CP induces no competitive advantage, neither competing tourism firm has an incentive to engage in CP.